Increased Fear Memory and Glutamatergic Modulation in Compulsive Drinker Rats Selected by Schedule-Induced Polydipsia - Prados-Pardo, Ángeles; Martín-González, Elena; Mora, Santiago; Merchán, Ana; Flores, Pilar; Moreno, Margarita (Frontiers in Behavioral Neuroscience, 2019)
Compulsive behavior is observed in several neuropsychiatric disorders such as obsessive-compulsive disorder, anxiety, depression, phobia, and schizophrenia. Thus, compulsivity has been proposed as a transdiagnostic symptom with a highly variable pharmacological treatment. Recent evidence shows that glutamate pharmacotherapy may be of benefit in impaired inhibitory control. The purpose of the present study was: first, to test the comorbidity between compulsivity and other neuropsychiatric symptoms on different preclinical behavioral models; second, to assess the therapeutic potential of different glutamate modulators in a preclinical model of compulsivity. Long Evans rats were selected as either high (HD) or low (LD) drinkers corresponding with their water intake in scheduled induced polydipsia (SIP). We assessed compulsivity in LD and HD rats by marble burying test, depression by forced swimming test, anxiety by elevated plus maze and fear behavior by fear conditioning test. After that, we measured the effects of acute administration (i.p.) of glutamatergic drugs: N-Acetylcysteine (25, 50, 100 and 200 mg/kg), memantine (3.1 and 6.2 mg/kg) and lamotrigine (15 and 30 mg/kg) on compulsive drinking on SIP. The results obtained showed a relation between high compulsive drinking on SIP and a higher number of marbles partially buried in marble burying test, as well as a higher percentage of freezing on the retrieval day of fear conditioning test. We did not detect any significant differences between LD and HD rats in forced swimming test, nor in elevated plus maze. The psychopharmacological study of glutamatergic drugs revealed that memantine and lamotrigine, at all doses tested, decreased compulsive water consumption in HD rats compared to LD rats on SIP. N-Acetylcysteine did not produce any significant effect on SIP. These results indicate that the symptom clusters of different forms of compulsivity and phobia might be found in the compulsive phenotype of HD rats selected by SIP. The effects of memantine and lamotrigine in HD rats point towards a dysregulation in the glutamatergic signaling as a possible underlying mechanism in the vulnerability to compulsive behavior on SIP. Further studies on SIP, could help to elucidate the therapeutic role of glutamatergic drugs as a pharmacological strategy on compulsive spectrum disorders.